1984
DOI: 10.1128/aac.25.2.283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of aztreonam in combination with newer beta-lactams and amikacin against multiply resistant gram-negative bacilli

Abstract: The in vitro synergistic activity of aztreonam in combination with piperacillin, moxalactam, cefotaxime, cefoperazone, and amikacin was examined against multiply resistant isolates of the family Enterobacteriaceae accommodating a volume of 1 ml of Mueller-Hinton broth (Difco Laboratories) were utilized. Each test isolate was grown overnight on sheep blood agar; then an inoculum of 5 x 105 CFU/ml was prepared by suspending growth to a predetermined optical density. Viable cell counts were performed with each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…The cumulative data, which are reviewed in great detail in subsequent sections of this article, suggest that beta-lactam combinations produce an enhanced killing effect versus Gram-negative pathogens, rivaling that of combination therapy with an aminoglycoside and beta-lactam (Bosso et al, 1991;Buesing and Jorgensen, 1984;Kurtz et al, 1981;Moody et al, 1984;Zinner et al, 1981). Yet, to date, there has been little investigation into the exact mechanism of enhanced killing/synergy with dual beta-lactam combinations.…”
Section: Potential For Greater Activity By Enhanced Binding To Penicimentioning
confidence: 92%
See 1 more Smart Citation
“…The cumulative data, which are reviewed in great detail in subsequent sections of this article, suggest that beta-lactam combinations produce an enhanced killing effect versus Gram-negative pathogens, rivaling that of combination therapy with an aminoglycoside and beta-lactam (Bosso et al, 1991;Buesing and Jorgensen, 1984;Kurtz et al, 1981;Moody et al, 1984;Zinner et al, 1981). Yet, to date, there has been little investigation into the exact mechanism of enhanced killing/synergy with dual beta-lactam combinations.…”
Section: Potential For Greater Activity By Enhanced Binding To Penicimentioning
confidence: 92%
“…Most of these studies used broth or agar dilution or the checkerboard method to test for synergy (Anderson et al, 1981;Baltimore et al, 1976;Bosso et al, 1990;Bosso et al, 1991;Buesing and Jorgensen, 1984;Chattopadhyay and Hall, 1979;Chen et al, 2004;Cleeland and Squires, 1983;Daschner and Hoffmann, 1982;Drusano et al, 1985;Fass, 1980;Fass, 1982aFass, , 1982bFoweraker et al, 2009;Fu and Neu, 1978;Tsuchiya, 1981a, 1981b;Kuck et al, 1981;Kurtz et al, 1981;Markowitz and Sibilla, 1983;Miles et al, 1981;Moody et al, 1984;Neu, 1982;Neu and Fu, 1978;Peterson et al, 1984;Sader et al, 2003;Schaad et al, 1982;Scheld et al, 1979;Scribner et al, 1982;Song et al, 2003;Stutman et al, 1984;Tybring and Melchior, 1975;van der Voet et al, 1983;Verbist and Verhaegen, 1984;Wu et al, 1984;Zinner et al, 1981), but time-kill studies were also done (Foweraker et al, 2009;Fu and Neu, 1978;Tsuchiya, 1981a, 1981b;Lister et al, 1998;Markowitz and Sibilla, 1983;…”
Section: In Vitro Data On Dual Beta-lactam Therapymentioning
confidence: 99%
“…A number of studies have reported positive outcomes for aztreonam and amikacin combinations and have successfully demonstrated synergy or partial synergy against gram-negative pathogens [6][7][8][9]. There are also published reports describing synergy against gram-negative isolates when aztreonam was tested in combination with either ciprofloxacin or levofloxacin [10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…AGENTS CHEMOTHER. Common duct 3.16 (2) bile Gallbladder bile 1.17 ± 0.32 (7) 3.26 ± 1.08 (6) The data document that therapeutic levels of aztreonam were present in several body tissues and fluids several hours after a single 2-g dose. The levels in most tissues and fluids were found to exceed the MICs for 90% of most susceptible aerobic and facultative gram-negative isolates at 6 h after drug administration.…”
mentioning
confidence: 76%